2013
DOI: 10.7770/ejee-v1n1-art519
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Production from Sugarcane Bagasse Pretreated by Steam Explosion

Abstract: Bioethanol is an alternative renewable fuel that can be produced from cellulosic biomass through hydrolysis and fermentation based processes. Sugarcane bagasse constitutes a potential lignocellulosic substrate for bioethanol production, since it has high sugar content and is a renewable, cheap and readily available feedstock. In this work, steam explosion pretreatment at different temperatures (200°C, 215°C and 230°C) for 5 min was evaluated on sugarcane bagasse for ethanol production by simultaneous saccharif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 32 publications
1
15
0
3
Order By: Relevance
“…Moreover, it has been reported that minor differences in the chemical composition of bagasse between the different varieties of sugarcane exist [32]. Amores et al [5] reported a total carbohydrate of 65% dry weight for sugarcane bagasse used in ethanol production. El-Tayeb et al [33] reported total carbohydrate composition of 86.9% w/w for bagasse.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it has been reported that minor differences in the chemical composition of bagasse between the different varieties of sugarcane exist [32]. Amores et al [5] reported a total carbohydrate of 65% dry weight for sugarcane bagasse used in ethanol production. El-Tayeb et al [33] reported total carbohydrate composition of 86.9% w/w for bagasse.…”
Section: Discussionmentioning
confidence: 99%
“…The use of steam explosion pre-treated bagasse is supported by several studies. Ferreira-Leitão et al [39] and Amores et al [5] have reported steam explosion pre-treatment for bagasse used as feedstock for ethanol production. Martin et al [40] reported bagasse pre-treatment by steam explosion using different impregnating agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Saccharum officinarum (sugarcane) bagasse is the solid remains obtained after the extraction of juice from the sugarcane [2,3,4]. Sugarcane bagasse is composed of: 43.6% by mass cellulose, 33.8% hemicellulose, 18.1% lignin, 2.3% ash and 0.8% wax on a dry weight basis [3,5].…”
mentioning
confidence: 99%